A new combination in Entada (Leguminosae) from Roraima, Brazil - Rodrigues, Rodrigo Schütz; Flores, Andréia Silva (Phytotaxa, 2012)
Entada simplicata, formerly recognized as a variety of E. polystachya, is reinterpreted as a distinct legume species, based on consistent differences regarding their leaves (number of pairs and width of leaflets), and fruits (mesocarp presence, stipe and funiculus length). Illustrations and a distribution map are provided for E. simplicata, which is endemic to Roraima State, northern Amazonia, Brazil.